Attitude, Subjective Norm, Spirituality and Internet-Triggered Academic Dishonesty (ITAD): A Case Study of Malaysian University Students - Norfhadzilahwati Rahim; Dato' Hasnah Hj Haron; Amalina Mursidi; Idris Gautama So; Anderes Gui (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025